Copper’s new role in cancer: how cuproptosis-related genes could revolutionize glioma treatment - Yu Wang; Sen Qiao; Ping Wang; Mi Li; Xiaozhen Ma; Hongmei Wang; Junhong Dong (BMC Cancer)
Abstract Objectives Cuproptosis, a novel form of regulatory cell death, was investigated in this study for its effects on cuproptosis-associated proteins during gliomas development, offering novel insights into the mechanism of copper ion-based antitumor drugs. Methods In the present study, bioinformatics and cellular experiments were employed to investigate cuproptosis-related genes (CRGs) in glioma, with a specific focus on SLC31A1. Results The study findings indicated that many CRGs (SLC31A1, FDX1, DLST, LIPT1, LIPT2, DLD, NFE2L2, ATP7A, DLAT, GCSH, and ATP7B) were differentially expressed between glioma and non-tumor groups. These genes potentially influence glioma initiation and progression by modulating associated signaling pathways, including those involved in cell cycle regulation, inflammatory responses, and the tumor microenvironment. Survival curve analysis and Cox proportional hazard regression model demonstrated that individuals classified as high-risk exhibited poorer prognosis, suggesting that CRGs possess prognostic capabilities. The assessment of tumor mutational burden indicated that CRGs could serve as biomarkers for predicting the efficacy of immunotherapy in glioma. Further functional analysis of SLC31A1 showed that its elevation was associated with increased glioma cell malignancy, promoting proliferation and migration. Additionally, treatment with the mitotic inhibitor MP-HJ-1b markedly suppressed SLC31A1 expression, consequently inhibiting glioma cell proliferation and migration. Conclusions Extensive data analysis indicated that CRGs hold promise as both prognostic markers and potential therapeutic targets for glioma.